2021
DOI: 10.1093/nsr/nwab218
|View full text |Cite
|
Sign up to set email alerts
|

Itch perception is reflected by neuronal ignition in the primary somatosensory cortex

Abstract: Multiple cortical areas including primary somatosensory cortex (S1) are activated during itch signal processing, yet cortical representation of itch perception remains unknown. Using a novel miniature two-photon microscopic imaging in free-moving mice, we investigated the coding of itch perception in S1. We found that pharmacological inactivation of S1 abolished itch-induced scratching behavior, and the itch-induced scratching behavior could be well predicted by the activity of a fraction of layer 2/3 pyramida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Optogenetic activation of cervical spinal GRPR 1 neurons induced laser frequency-dependent scratching behavior (Fig. 5A-F), indicating that optogenetic manipulation of spinal GRPR 1 neurons successfully induced the itch sensation, consistent with recent studies (Liu et al, 2019;Chen et al, 2022). Next, we wondered how to separate the itch sensation and itch relief.…”
Section: Dynamics Of Dopamine Signals In the Nac Lash Under Different...supporting
confidence: 82%
See 1 more Smart Citation
“…Optogenetic activation of cervical spinal GRPR 1 neurons induced laser frequency-dependent scratching behavior (Fig. 5A-F), indicating that optogenetic manipulation of spinal GRPR 1 neurons successfully induced the itch sensation, consistent with recent studies (Liu et al, 2019;Chen et al, 2022). Next, we wondered how to separate the itch sensation and itch relief.…”
Section: Dynamics Of Dopamine Signals In the Nac Lash Under Different...supporting
confidence: 82%
“…Nevertheless, the dopamine release in the NAc LaSh at the onset of itch stimulation likely represents the motivational component. Although we cannot exclude the possibility that activation of spinal GRPR 1 neurons could elicit other sensations, it is conceivable that pruritic input should be dominant during optogenetic activation of spinal GRPR 1 neurons (Liu et al, 2019;Chen et al, 2022). Thus, the evidence provided in this study together with previous studies suggests that dopaminergic signals have a role in both the motivation and reward components of itch.…”
Section: Discussionmentioning
confidence: 46%
“…Perception of sensation is generated at the brain level, and processing of somatosensory information involves multiple brain regions [ 13 , 14 ]. Primary somatosensory cortex (S1) plays a crucial role in the perception and discrimination of somatosensory information, including touch, itch, and pain [ 15 - 17 ]. Recent studies have shown that S1 encodes the sub-modality of somatic sensations using multiplexed strategies [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%